Sulfoximine- and Sulfilimine-Based DAPSON Analogues; Syntheses and Bioactivities - Chen, Xiao Yun; Buschmann, Helmut; Bolm, Carsten (Synlett, 2012)
Sulfoximine- and sulfilimine-based diamino-diphenyl sulfone (DAPSON) analogues have been prepared and their COX-1 and COX-2 inhibition potencies as well as LTB4 and TNF binding properties were studied. Furthermore, their antiproliferative activities on cancer cell growth were investigated. Neither compounds showed significant bioactivities.
Keywords: drug discovery; cancer; oxidation; sulfoximine; sulfilimine